2021
DOI: 10.3390/app112210719
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Review on Micro-Implants and Their Use in Orthodontics and Dentofacial Orthopaedics

Abstract: The aim of this study was to review the literature and evaluate the failure rates and factors that affect the stability and success of temporary anchorage devices (TADs) used as orthodontic anchorage. Data was collected from electronic databases: MEDLINE database and Google Scholar. Four combinations of term were used as keywords: “micro-implant”, “mini-implant”, “mini-screw”, and “orthodontics”. The following selection criteria were used to select appropriate articles: articles on implants and screws used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 75 publications
0
7
0
4
Order By: Relevance
“…Many orthodontists avoid using mini-implants due to fear of failure and limitations of surgical skills [ 12 ]. Providing a more accurate alternative to free hand insertion could encourage clinicians to take this method into consideration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many orthodontists avoid using mini-implants due to fear of failure and limitations of surgical skills [ 12 ]. Providing a more accurate alternative to free hand insertion could encourage clinicians to take this method into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Although anchorage control is the main use of mini-implants in orthodontics, studies have reported successful use of these devices as support for provisional crowns as an alternative to bonded bridges and dentures, in both growing and adult patients [ 12 , 13 ]. Being one of the most prevalent missing anterior teeth, the majority of studies describe this method for the replacement of the upper lateral incisor [ 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to several studies, the nanostructured surface has a larger surface area than the microstructured surface, leading to better osseointegration. 19 , 23 The nanotube TiO 2 layer produced by anodizing treatment has enough space to store various chemicals, including drugs. The space of the nanotube can be used as a carrier for delivery of drugs or bioactive materials.…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency of these methods frequently depends on patient cooperation. Alternatively, micro‐implants (MIs), also referred to as temporary anchorage devices (TADs), mini‐implants, or mini‐screws have been used to achieve challenging orthodontic movements, including guiding osteo‐distractions, stabilizing an edentulous premaxilla, and moving teeth into atrophic alveolar sites 1 . Orthodontic mini‐implants can be a helpful tool to solve difficult malocclusion problems that require excessive anchorage force.…”
Section: Introductionmentioning
confidence: 99%